Are you well-Informed? evaluating the information signage at the Kuching Waterfront, Sarawak: A preliminary study / Wan Juliana Emeih Wahed and Patricia Pawa Pitil - Wahed, Wan Juliana Emeih; Pitil, Patricia Pawa (Faculty of Art and Design, 2020)
Sarawak is a place that everyone should visit as this state is one of the most unassuming regions, with an interesting blend of historical attractions. Kuching Waterfront is the primary location to visit in Kuching city. It is an esplanade that stretches for about 900 meters along the south bank of the Sarawak River. It attracts locals and tourists as it offers a variety of food stalls, museums, street entertainment, and excellent views. In this regard, well-informative signage allocated at Kuching Waterfront is crucial, and should deliver various types of information: historical details, maps, and other features. Therefore, this study's objective was to evaluate the information signage at Kuching Waterfront by interviewing visitors and through observation made by the researchers. The findings obtained revealed that there is a need to revise or upgrade existing information signage. The study also highlights the necessity for the information signage to be more readable, informative and attract readers or viewers who could be tourists or pedestrians along the Kuching Waterfront. Collaboration between related bodies of the state tourism board or other agencies and designers to build information signage can be taken into consideration to enhance the main attraction of the city and make it more informative and appealing.